Effects of Lumbar Stiffness After Lumbar Fusion Surgery on Activities of Daily Living. Issue 8 (April 2016) - Kimura, Hiroaki; Fujibayashi, Shunsuke; Otsuki, Bungo; Takahashi, Yoshimitsu; Nakayama, Takeo; Matsuda, Shuichi
Abstract : Study Design: A retrospective cohort study. Objective: The aim of this study was to assess the effects of lumbar stiffness after lumbar fusion surgery on functional limitations, health-related quality of life, and activities of daily living (ADL). Summary of Background Data: Postoperative outcomes after fusion surgery are usually assessed using patient-reported instruments to describe disability related to pain and health status. There are few studies on the effects of lumbar stiffness on ADL after lumbar fusion surgery. Methods: This study included 93 patients who underwent lumbar fusion surgery for degenerative lumbar disease. Their mean age was 69 years (range 51–79), and the mean follow-up was 34 months (24–46). The patients were categorized into 5 groups according to the number of segments involved: 0 level (decompression), 1 level, 2 levels, 3 levels, and 4 levels. They completed a 21-item questionnaire about their ADL and the Short Form Health Survey 36 (SF-36) to evaluate the effects of lumbar stiffness on ADL after surgery. Results: There was a linear trend toward a decreased rating in all items in our questionnaire and in the physical component summary in the SF-36 related to postoperative lumbar stiffness. These trends were significantly related to the number of fused segments ( P < 0.05 and P < 0.001, respectively). Patient satisfaction did not differ between the groups ( P = 0.381). Patients who received a 1- or 2-level fusion reported no serious limitations in most ADL. Patients who received a 3- or 4-level fusion, especially 4-level fusion, reported more limitations because of postoperative lumbar stiffness. Conclusion: This study investigated in detail the effects of lumbar stiffness after fusion surgery on ADL. Spine surgeons should consider the patient's occupation and lifestyle in preoperative planning. These results will help the surgeon explain the possible outcomes to patients planning to undergo fusion surgery. Level of Evidence: 2 Abstract : Supplemental Digital Content is available in the text